DEVELOPMENT OF CALCULUS LEARNING MEDIA BASED ON TIMOR ISLAND LOCAL WISDOM WITH SCILAB IMPLEMENTATION - Zulkaidah Nur Ahzan; Justin Eduardo Simarmata (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
Abstract :This study aims to develop learning media for calculus based on the local wisdom of Timor Island with the implementation of Scilab. In addition, the research conducted simulations and compared the conventional methods and Scilab programming language to solve calculus problems. It is crucial to provide knowledge and insight to students to perform various types of simulations related to mathematics using Scilab or other open-source-based programming languages, besides the students become accustomed to solving mathematical problems with the help of programming languages. Twenty-three students of the Department of Mathematics Education in the University of Timor participated in this study to define, design, and develop a learning media in the form of handouts and powerpoints. The subject experts assessed the developed media as